2014
DOI: 10.1016/j.jpainsymman.2013.12.246
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Initial Palliative Prognostic Index and Score Change Provides a Better Prognostic Value for Terminally Ill Cancer Patients: A Six-Year Observational Cohort Study

Abstract: Combination of initial PPI and score change is more useful than initial PPI for identifying patients with poor outcomes in good prognostic groups and patients with better outcomes in poor prognostic groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 28 publications
0
32
0
1
Order By: Relevance
“…The median survival rate was 53 days with an improvement in PPI score, 36 days with a stable PPI score, and 22 days with PPI deterioration over the 1-week period. 79 The C-statistic for 30-day survival was 0.63 for a baseline PPI score, 0.64 for a PPI change score, and 0.71 for the combined baseline and change in PPI. 79 When only patients with a higher baseline PPI (ie, > 6) were included, the C-statistics for 30-, 60-, and 90-day survival rates were 0.66, 0.64, and 0.63 for the baseline PPI, respectively, and 0.72, 0.76, and 0.79 for the magnitude of PPI change between baseline and day 8.…”
Section: Actuarial Estimation Of Survivalmentioning
confidence: 94%
See 2 more Smart Citations
“…The median survival rate was 53 days with an improvement in PPI score, 36 days with a stable PPI score, and 22 days with PPI deterioration over the 1-week period. 79 The C-statistic for 30-day survival was 0.63 for a baseline PPI score, 0.64 for a PPI change score, and 0.71 for the combined baseline and change in PPI. 79 When only patients with a higher baseline PPI (ie, > 6) were included, the C-statistics for 30-, 60-, and 90-day survival rates were 0.66, 0.64, and 0.63 for the baseline PPI, respectively, and 0.72, 0.76, and 0.79 for the magnitude of PPI change between baseline and day 8.…”
Section: Actuarial Estimation Of Survivalmentioning
confidence: 94%
“…79 The C-statistic for 30-day survival was 0.63 for a baseline PPI score, 0.64 for a PPI change score, and 0.71 for the combined baseline and change in PPI. 79 When only patients with a higher baseline PPI (ie, > 6) were included, the C-statistics for 30-, 60-, and 90-day survival rates were 0.66, 0.64, and 0.63 for the baseline PPI, respectively, and 0.72, 0.76, and 0.79 for the magnitude of PPI change between baseline and day 8. 80 The corresponding accuracy rates were 61%, 57%, and 55% for baseline PPI, and 71%, 79%, and 83% for PPI change, respectively.…”
Section: Actuarial Estimation Of Survivalmentioning
confidence: 94%
See 1 more Smart Citation
“…The majority of them were originally developed to estimate the prognosis of patients with days to weeks of survival. [19][20][21][22][23][24] To the best of our knowledge, no other prognostic tool has been designed to target outpatients when they are first referred to PC. From the available prognostic tools, the modified Glasgow Prognostic Score (mGPS), 25 phase angle, 26 and performance status scales 27 were externally validated in populations of cancer patients with median survival times longer than 2-3 months.…”
Section: Discussionmentioning
confidence: 99%
“…Some scholars hold the view that a oneshot PPI assessment might not be accurate enough as a prognostic tool because patients' clinical features changed dynamically during the end-of-life trajectory. [47][48][49] Arai et al [49] reported a retrospective cohort study that reassessment of the PPI was necessary because of the change in the PPI as an important and independent factor associated with the survival of advanced cancer patients. Another previous study reported by Kao et al [48] showed that the combination of initial PPI and score change was more accurate to predict the actual prognosis.…”
Section: Accuracy Of the Three Prognostic Toolsmentioning
confidence: 99%